Pengaruh Shopping Lifestyle, Fear of Missing Out (FOMO) dan Electronic Word of Mouth (E-Wom) Terhadap Impulse Buying Produk Body Lotion Scarlett pada Pengguna Marketplace Tiktok Generasi Z di Surabaya - Sabela Kirana Widyadhana; Ayun Maduwinarti; Ute Chairuz Nasution (Indo Publishing, 2026)
The purpose of this study is to examine the influence of shopping lifestyle, fear of missing out (FoMO), and electronic word of mouth (E-WoM) on impulse buying of Scarlett body lotion among Generation Z users of the TikTok marketplace in Surabaya. This study employs a quantitative method using non-probability sampling through a purposive sampling approach. The sample in this study consisted of 96 respondents who are Generation Z in Surabaya and have purchased Scarlett body lotion products through the TikTok marketplace. Data collection was conducted using an e-questionnaire distributed via Google Forms. The analytical procedures applied in this study comprised instrument validation, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination evaluation using SPSS version 27. The study results suggest that shopping lifestyle positively and significantly influences impulse buying. Likewise, Fear of Missing Out (FoMO) positively and significantly affects impulse buying. Moreover, Electronic Word of Mouth (E-WoM) positively and significantly contributes to impulse buying behavior. Simultaneously, shopping lifestyle, Fear of Missing Out (FoMO), and Electronic Word of Mouth (E-WoM) have a significant effect on impulse buying of Scarlett body lotion among Generation Z TikTok marketplace users in Surabaya.